2022
DOI: 10.1002/cpe.6899
|View full text |Cite
|
Sign up to set email alerts
|

A model‐based approach to user preference discovery in multi‐criteria recommender system using genetic programming

Abstract: Multi-criteria recommender systems (MCRSs) provide suggestions to users based on their preferences to various criteria. Incorporation of criteria ratings into recommendation framework can provide quality recommendations to users because these ratings can elicit users' preferences efficiently. However, elicitation of user's overall preference based on criteria ratings is a key issue in MCRS. Even though several aggregation methods for the elicitation of users' overall preference have been investigated in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Similar to the CF technique, the MCRS has been classified as memory-based and model-based approaches [ 2 ]. The model-based approach involves developing a system that identifies a function that determines how single criteria and multi-criteria ratings relate to one another [ 14 ]. On the other hand, the memory-based approach expands traditional RS by identifying user similarities based on different criteria and aggregating these similarities using different methods.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the CF technique, the MCRS has been classified as memory-based and model-based approaches [ 2 ]. The model-based approach involves developing a system that identifies a function that determines how single criteria and multi-criteria ratings relate to one another [ 14 ]. On the other hand, the memory-based approach expands traditional RS by identifying user similarities based on different criteria and aggregating these similarities using different methods.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Results showed that the GA-based approaches gave better performance and the multi-heuristic GA-based approach outperformed other approaches. On the other hand, GP was employed in MCRS to learn criteria weights [ 14 , 19 ]. Where GP was used to learn a function to transform user preferences into an aggregate of criteria ratings.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation